2003
DOI: 10.1088/0026-1394/40/1/351
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of filter radiometers with a wavelength-tunable laser source

Abstract: Results of filter radiometer characterization with a wavelength-tunable Ti : sapphire laser in the wavelength band around 900 nm are presented. The effect of interference between the reflections from filter surfaces in the case of coherent laser light was studied and reduced with a special filter design with antireflection coatings. Measuring the responsivity as a function of wavelength over a very narrow band was used to reveal the remaining interference effects. Uncertainty analysis and test results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…It has been demonstrated that the use of a specific interference filter with wedged and anti-reflection (AR) coated output faces can reduce the amplitude of the laser intensity modulation by a factor of 20 [17,18]. For this reason, our interference filter has Despite these precautions, the recorded spectral transmission of the pyrometer around λ = 800 nm exhibits an intensity modulation caused by residual interferences with a poor modulation contrast C = 3 % and a periodicity δλ = 0.2 nm (Fig.…”
Section: Interferences Observed On the Pyrometer Spectral Responsivitmentioning
confidence: 99%
“…It has been demonstrated that the use of a specific interference filter with wedged and anti-reflection (AR) coated output faces can reduce the amplitude of the laser intensity modulation by a factor of 20 [17,18]. For this reason, our interference filter has Despite these precautions, the recorded spectral transmission of the pyrometer around λ = 800 nm exhibits an intensity modulation caused by residual interferences with a poor modulation contrast C = 3 % and a periodicity δλ = 0.2 nm (Fig.…”
Section: Interferences Observed On the Pyrometer Spectral Responsivitmentioning
confidence: 99%
“…The FR2-800 radiometer was characterized as a whole package with the help of a wavelength-tunable Ti:sapphire laser. The characterization method is described in more detail in [11].…”
Section: Filter Radiometersmentioning
confidence: 99%
“…The power responsivity determination of the trap detector was done by a laser calibration: the responsivity was measured at four different laser wavelengths, and a responsivity model was used to extend the calibration over the whole wavelength range. FR2-800 was calibrated using a wavelength-tunable laser [11], which results in somewhat lower wavelength and responsivity uncertainties than those of the other filter radiometers. The uncertainty of the responsivity model is between 0.06% and 0.365%, depending on the wavelength.…”
Section: Filter Radiometersmentioning
confidence: 99%
“…These measurements are conventionally realized with monochromator-based facilities using high power lamps as radiant sources. However, due to the rapid progress in laser technology, lamp-monochromator-based setups can already be replaced by tunable laser facilities [1][2][3][4][5]. Tunable lasers allow for much higher spectral irradiance levels with smaller bandwidths for the measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the Physikalisch-Technische Bundesanstalt (PTB), a number of other national metrology institutes (including the National Physical Laboratory in the UK [1], the National Institute of Standards and Technology in the USA [2], Mittatekniikan keskus in Finland [3], and the Federal Office of Metrology in Switzerland [4], among others) have built tunable laser-based measurement facilities for the calibration and characterization of radiometric detectors. In those setups, different types of laser systems are used.…”
Section: Introductionmentioning
confidence: 99%